Digital accounting: an analysis on the use of technology in accounting offices and digital services provided during the Covid-19 pandemic - Silva, Agilson Emerson da (2023)
In summary, Digital Accounting is nothing more than the accounting services being offered digitally, that is, the use of technology to provide services in a 100% digital way. This study seeks to analyze whether there has been a change in the provision of accounting services, in addition to observing if, during the Covid-19 pandemic, there was a greater adhesion of digital accounting by the offices in Nova Serrana. To test the hypotheses raised, a questionnaire was applied to a sample equivalent to 50% of the accounting firms that exist in the city, which corresponds to 21 offices. With the results, it was analyzed that the firms are aware that investing in technology is important, but the adherence to digital accounting was not as significant as the provision of services in a hybrid way.